ОВООТЫН ОРДЫН ГЕОЛОГИЙН ТОГТОЦ, НҮҮРСНИЙ ЧАНАР - Б.ЭРДЭНЭЦОГТ; Б.БАРСБОЛД (Geological Issues, 2023)
Ovoot deposit is located in Orkhon-Selenge coal bearing area and coal measures are hosted in Lower-Middle Jurassic sequences. The deposit has three main seams, which form syncline structure. Thicknesses of the seams increase from north (1.5 m) to south of the deposit (62 m). Ovoot coal, classified as Zh and KZh type, has high vitrinite content, which provides the coal with high fluidity and plastic properties. Results of pilot scale tests show that at an average washing yield of 82%, a 9% ash, with 10% moisture product would be achievable from Ovoot coal. The pilot scale coke oven tests show that in coke batches including coke breeze, the addition of the Ovoot coking coal can be used to replace premium hard coking coal and improve overall coke quality. In particular, a significant improvement in overall coke performance was achieved with blending semi-soft coking coal with relatively smaller proportions of Ovoot coking coal. This provides the potential for Ovoot coking coal to be used in blends to upgrade similar rank thermal and low caking semi-soft coals from Mongolia’s South Gobi region to improve the overall quality of Mongolia’s coking coal exports. Coal reserves of Ovoot are estimated to be 255 million tons with 188 million tons of marketable coal reserves at approximately 10%> ash contents. This indicates that Ovoot is the second largest coking coal reserve in Mongolia after Tavantolgoi deposit.